GEOLOGICAL EVOLUTION OF OLIGOCENE TO PLEISTOCENE LEBAKSIUH, WEST JAVA, INDONESIA - Sandyputra, Adryan Ridho; Sunardy, Edy; Ilmi, Nisa Nurul (Universitas Padjadjaran, 2026)
This study intends to map and analyze the geological conditions in Lebaksiuh, Sidamukti, and the surrounding area of Sumedang and Majalengka Regencies, West Java, Indonesia. The methods used include field observation, laboratory analysis, and literature review. The geomorphological units comprises steep high volcanic uplands, steep high structural uplands, steep low structural hills, and gently sloping denudational lowland, with sub-dendritic, radial, and modified trellis drainage patterns occupying most of the area. Field observation data shows that the area consists of 5 lithostratigraphic units which are the andesite Unit (HA), claystone Unit (NMCSH), sandstone Unit (NPCS), tuff Unit (NPCT), and alluvium unit (Qa). The geological evolution that starts with the formation of the Oligocene andesite unit (HA). Then deposition of the Cinambo shale unit (NMCSH) in early Miocene with a deep marine depositional environment, then an Intra-Miocene tectonic activity compresses the region, followed by a compressional release in the Miocene-Pliocene age and sea regression phase that shaped the local basin. In the Pliocene, Citalang sand (NPCS) and tuff unit (NPCT) are deposited in a fluvial depositional environment. Reactivation of the older faults happened after the deposition. lastly accumulation of the alluvium unit (QA) in the Quaternary Holocene age. Structural geology plays a huge role in the area with a regional thrust fault that divides the Citalang and Cinambo formation in the south which showed an arcing pattern that opens to the north, and a more local fold structure that arced mostly in north-south direction, and fault structures present in the citalang formation. Potential geological resources in the area are Sand and andesite, and can be used for building material. Contrastingly, the geological hazards include landslides and earthquakes.